Karyological Investigation of Sixteen Cirsium Mill. (Asteraceae, Cardueae) Taxa from Turkey - Kiran, Yasar (Univ Tokyo Cytologia, 2018)
The chromosome number and karyotype analysis of sixteen taxa of genus Cirsium Mill. distributed in Turkey were analyzed. This taxa are, Cirsium steriolepis Petr., C. bulgaricum DC., C. polycephalum DC., C. trachylepis Boiss., C. sommieri Petr., C. osseticum (Adams) Petrak, C. leucocephalum (Willd.) Spreng ssp. tenuilobum (K. Koch) Greuter, C. haussknechtii Boiss., C. ekimianum Yildiz & Dirmenci, C. handaniae Yildiz, Dirmenci & Arabaci, C. davisianum Kit Tan & Sorger, C. hypoleucum DC., C. pseudopersonata Boiss & Bal. ssp. pseudopersonata, C, pseudopersonata Boiss. & Bal. ssp. kuznezowianum (Somm. & Lev.) Petrak, C. canum (L.) All., C. obvallatum (Bieb.) Fischer, and nine of them are endemic species (C. steriolepis, C. polycephalum, C. trachylepis, C. sommieri, C. leucocephalum ssp. tenuilobum, C. davisianum, C. handaniae, C. ekimianum and C. pseudopersonata ssp. pseudopersonata). The somatic chromosome number of all studied taxa were determeined as 2n=2x=34. Total chromosome lengths varied 68.00 to 147.92 mu m among species. Karyotype asymmetry indices other parameters were also calculated. Karyotype analysis indicated that Cirsium taxa generally have median (m and M) chromosomes. In addition, only C. davisianum species has one submedian (sm) chromosome. The chromosome number and karyotype of C. polycephalum, C. handaniae, C. davisianum and C. ekimianum are newly reported.
Keywords: Asteraceae; Cirsium; Karyotype; Chromosome number; Turkey